Effect of Self-instructional Modules on Social Science (Geography) Achievement of Secondary School Students in Relation to their Intelligence and Gender - Chauhan, Poonam; Satyarthi, Geetanjali Satendra (JOURNAL OF INDIAN EDUCATION, 2019)
In this study, the researcher studies the effect of Self-instructional Modules on social science (Geography) achievement of Class IX students in relation to their intelligence and gender. The sample is selected from three secondary schools of Agra district, UP, India. The sample comprises 320 students. Pretest and post-test equivalent group design of true experimental research is used to find the answers to the problem. For testing achievement, self-made achievement test is used by the researcher. J C Raven’s Standard Progressive Matrices test is used for the assessment of intelligence in this study. For data analysis, t-test and Pearson correlation and ANCOVA techniques are used through SPSS. The researcher finds out that there is no significant difference in academic achievement in terms of gender. Boys and girls have performed equally in terms of achievement. Secondly, there is no significant difference in intelligence in terms of gender. Boys and girls have equal intelligence. Also, there is no significant relationship between academic achievement and intelligence. Self-instructional Modules are found to be more effective than the traditional teaching method.